KONTRIBUSI KELINCAHAN DAN KECEPATAN TERHADAP KETERAMPILAN MENGGIRING BOLA PADA TIM FUTSAL SMA AL-HUDA PEKANBARU - M. Agung Wiguna; Zainur Zainur; Aref Vai (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: The purpose of this study was to determine how much the contribution of agility, and speed to dribbling skills on the futsal team SMA Al-Huda Pekanbaru. In this research, Pearson product moment correlation technique is used, namely the two intervals scale variables. The population in this study were all students who participated in futsal extracurricular activities at the SMA Al-Huda Pekanbaru, which numbered 15 people. In this research using total sampling. From the results of the calculation of the correlation between agility with the ability to herd obtained r relationship between agility to dribble futsal players SMA Al-Huda Pekanbaru. Speed has a significant relationship with the ability to dribble futsal players SMA Al-Huda Pekanbaru, marked by the results obtained are obtained rcount (0.9357)> rtable (0.525). There is a significant correlation together between agility and speed with the ability to dribble futsal players SMA Al-Huda Pekanbaru. This is indicated by the results obtained by Fcount 14.32> Ftable 3.34.Key words: Agility, Speed, Dribbling